Genetic underpinnings in Alzheimer’s disease – A review - Moustafa, Ahmed A.; Hassan, Mubashir; Hewedi, Doaa H.; Hewedi, Iman; Garami, Julia K.; Al Ashwal, Hany; Zaki, Nazar; Seo, Sung-Yum; Cutsuridis, Vassilis; Angulo, Sergio L.; Natesh, Joman Y.; Herzallah, Mohammad M.; et al. (Walter de Gruyter GmbH, 2017)
In this review, we discuss the genetic etiologies of Alzheimer’s disease (AD). Furthermore, we review genetic links to protein signaling pathways as novel pharmacological targets to treat AD. Moreover, we also discuss the clumps of AD-mediated genes according to their single nucleotide polymorphism mutations. Rigorous data mining approaches justified the significant role of genes in AD prevalence. Pedigree analysis and twin studies suggest that genetic components are part of the etiology, rather than only being risk factors for AD. The first autosomal dominant mutation in the amyloid precursor protein (APP) gene was described in 1991. Later, AD was also associated with mutated early-onset (presenilin 1/2, PSEN1/2 and APP) and late-onset (apolipoprotein E, ApoE) genes. Genome-wide association and linkage analysis studies with identified multiple genomic areas have implications for the treatment of AD. We conclude this review with future directions and clinical implications of genetic research in AD.